PENGARUH TAX AVOIDANCE DAN INOVASI TERHADAP NILAI PERUSAHAAN - Devina Juliani Putri; Estralita Trisnawati (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research aims at the role of tax avoidance and innovation implementation toward firm value on food and beverage industry listed on the Indonesia Stock Exchange during 2014-2019. Sample was selected using purposive sampling method and the valid data was 13companies. Data processing techniques using multiple regression analysis with the help ofSPSS program (Statistical Product and Service Solution) for Windows, SmartPLS 3.0 and Microsoft Excel 2016. The results of this study indicate that tax avoidance have a significant influence on firm value positively and innovation does not have significant influence on firm value. The implication of this study is that tax avoidance that companies does to reduce tax burden will increase the firm value and that innovation does not increase firm value.